2012
DOI: 10.1002/cbf.2925
|View full text |Cite
|
Sign up to set email alerts
|

Digestive cells from Mytilus galloprovincialis show a partial regulatory volume decrease following acute hypotonic stress through mechanisms involving inorganic ions

Abstract: The response of isolated digestive cells of the digestive gland of Mytilus galloprovincialis to hypotonic shock was studied using videometric methods. The isolated cells exposed to a rapid change (from 1100 to 800 mosmol kg(-1) ) of the bathing solution osmolality swelled but thereafter underwent a regulatory volume decrease (RVD), tending to recover the original size. When the hypotonic stress was applied in the presence of quinine and glibenclamide, known inhibitors of swelling activated ion channels, the ce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
24
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 58 publications
(25 citation statements)
references
References 46 publications
1
24
0
Order By: Relevance
“…In many cell types, including bivalves [35], this behaviour is typically mediated by potassium and chloride electroneutral co-transport as well as VRAC (Volume-Regulated Anion Channels) which are typically inactive under resting conditions, but are able to contribute to a partial recovery of the cell size by a regulatory volume decrease mechanism in cells subjected to hypotonic stress [3638]. …”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In many cell types, including bivalves [35], this behaviour is typically mediated by potassium and chloride electroneutral co-transport as well as VRAC (Volume-Regulated Anion Channels) which are typically inactive under resting conditions, but are able to contribute to a partial recovery of the cell size by a regulatory volume decrease mechanism in cells subjected to hypotonic stress [3638]. …”
Section: Discussionmentioning
confidence: 99%
“…For example, by using videometric methods it has been demonstrated that the cells from the digestive glands of M . galloprovincialis , exposed to rapid changes of the bathing solution (from 1100 to 800 mosmol/kg), undergo to a process of regulatory volume decrease [35]. Possibly the minor movements of M .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In order to identify and quantify the different metabolites that determine and characterise a precise foodstuff in its particular state, the approach that seems the most reliable is that of Metabolomics (Lindon et al 2007). The metabolism represents the physical and chemical reactions that occur in a living organism, so that its metabolic content is important for a comprehensive analysis of all metabolite changes upon stimuli (Lindon et al 2007) or stress conditions (Torre et al 2013). Indeed, the knowledge of the metabolite content can be used for the characterisation of a given foodstuff in its particular state.…”
Section: Introductionmentioning
confidence: 99%
“…This regulatory response is called “regulatory volume decrease” (RVD). Volume-regulatory behavior has been observed in: cells isolated from digestive glands of Mytilus galloprovincialis (Torre et al, 2013), Gobius niger enterocytes (Trischitta et al, 2004), Anguilla anguilla enterocytes (Trischitta et al, 2005), turbot hepatocytes (Ollivier et al, 2006), Ehrlich ascites tumour cells (Hoffmann, 1984), and mammalian red blood cells (Ellory et al, 1985) exposed to osmotic stress.…”
Section: Introductionmentioning
confidence: 99%